Systematic review on chronic non-communicable disease in disaster settings - Christine Ngaruiya; Robyn Bernstein; Rebecca Leff; Lydia Wallace; Pooja Agrawal; Anand Selvam; Denise Hersey; Alison Hayward (BMC, 2022)
Abstract Background Non-communicable diseases (NCDs) constitute the leading cause of mortality globally. Low and middle-income countries (LMICs) not only experience the largest burden of humanitarian emergencies but are also disproportionately affected by NCDs, yet primary focus on the topic is lagging. We conducted a systematic review on the effect of humanitarian disasters on NCDs in LMICs assessing epidemiology, interventions, and treatment. Methods A systematic search in MEDLINE, MEDLINE (PubMed, for in-process and non-indexed citations), Social Science Citation Index, and Global Health (EBSCO) for indexed articles published before December 11, 2017 was conducted, and publications reporting on NCDs and humanitarian emergencies in LMICs were included. We extracted and synthesized results using a thematic analysis approach and present the results by disease type. The study is registered at PROSPERO (CRD42018088769). Results Of the 85 included publications, most reported on observational research studies and almost half (48.9%) reported on studies in the Eastern Mediterranean Region (EMRO), with scant studies reporting on the African and Americas regions. NCDs represented a significant burden for populations affected by humanitarian crises in our findings, despite a dearth of data from particular regions and disease categories. The majority of studies included in our review presented epidemiologic evidence for the burden of disease, while few studies addressed clinical management or intervention delivery. Commonly cited barriers to healthcare access in all phases of disaster and major disease diagnoses studied included: low levels of education, financial difficulties, displacement, illiteracy, lack of access to medications, affordability of treatment and monitoring devices, and centralized healthcare infrastructure for NCDs. Screening and prevention for NCDs in disaster-prone settings was supported. Refugee status was independently identified both as a risk factor for diagnosis with an NCD and conferring worse morbidity. Conclusions An increased focus on the effects of, and mitigating factors for, NCDs occurring in disaster-afflicted LMICs is needed. While the majority of studies included in our review presented epidemiologic evidence for the burden of disease, research is needed to address contributing factors, interventions, and means of managing disease during humanitarian emergencies in LMICs.